The Relationship of Knowledge, Attitudes, and Peer Support to the Prevention of Risky Sexual Behavior in Students at SHS 1 Subang - Reynaia Putri, Keisha; Handayani, Fitri; Ratna Palupi, Eva Riantika; Angga Kusuma, M. Iqbal (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Adolescents are a vulnerable group to risky sexual behaviors due to a lack of understanding of reproductive health. Objective: To determine the relationship between knowledge, attitudes, and peer support and risky sexual behavior in adolescents at SHS 1 Subang. Methods: The study used a quantitative method with a cross-sectional design  and a correlational approach. A sample of 87 respondents was selected through the proportionate stratified random sampling technique. Results and Discussion: The results of the analysis using the Spearman Rank Corelation  test showed that there was a significant relationship between knowledge (r 0.407; p-value < 0.001 (p < 0.05), attitude (r 0.310; p-value 0.003 (p < 0.05), and peer support (r 0.413; p-value < 0.001 (p < 0.05) with risky sexual behavior. Conclusion: Knowledge, attitudes, and peer support have an important role in shaping adolescent sexual behavior, in accordance with the Precede-Proceed Model theory  which states that behavior is influenced by predisposing and reinforcing factors.